Teoria das ruas completas aplicada à avaliação da infraestrutura de sistemas urbanos de transporte - Lázaro, Bruno de Oliveira (2022)
This research aims to evaluate the infrastructure of urban transport systems based on the guidelines proposed by the Complete Streets Theory. Therefore, a case study was developed along Segismundo Pereira Avenue, an important road axis located in the eastern sector of the city of Uberlândia/MG, Brazil. Using geotechnologies, georeferenced location data were collected from the main urban infrastructure equipment in the study area. In addition, orbital images were acquired for urban characterization of the region surrounding the analyzed road. The information collected was organized in the form of a geocoded digital database. The observations from this database were evaluated by designing and applying an evaluation matrix, developed based on literature recommendations for the design, operation and management of complete streets. The matrix was statistically statistically through cluster analysis and spatial dispersion analysis. The products resulting from this evaluation were spatialized in the QGIS 3.16.6 software for the elaboration of thematic maps of the study area. The results obtained allow us to observe that the urban transport infrastructure elements of the road studied in this research are spatially distributed in a very heterogeneous way. Thus, regions closer to the beginning of Segismundo Pereira Ave have transport infrastructure more in line with the urban configuration of a complete street, while regions closer to the end of the street behave in a way that is dissonant to this configuration. However, it was possible to conclude that; in general, the urban transport infrastructure of the avenue develops efficiently, ensuring good traffic conditions within the context of smart and accessible urban mobility.